Tropilaelaps mite Tropilaelaps spp. Delfinado & Baker (Arachnida: Mesostigmata: Laelapidae) - Ashley N. Mortensen; Sarah Burleson; Gunasegaran Chelliah; Ken Johnson; Daniel R. Schmehl; Jamie D. Ellis (EDIS)
Honey bees throughout the world are exposed to numerous pests, parasites, and pathogens. One such parasite is Tropilaelaps spp. Delfinado & Baker, an ectoparasitic mite that feeds on the hemolymph of developing honey bees. Four species of Tropilaelaps have been identified and characterized. This 4-page fact sheet was written by Ashley N. Mortensen, Sarah Burleson, Gunasegaran Chelliah, Ken Johnson, Daniel R. Schmehl, and Jamie D. Ellis, and published by the UF Department of Entomology and Nematology, October 2014. (Photo credit: Pest and Diseases Image Library, Bugwood.org)